A District Beginner Teacher Induction Initiative in South Africa: the Pressure and Support Contestation - Kadenge, Emure (Perspectives in education, 2021)
The main aim of this paper is to explore an approach to beginner teacher induction in a Johannesburg, South Africa education district’s induction programme. It focuses on how the idea of beginner teacher induction is conceptualised by examining the district induction programme’s teaching form and foci. Data were collected through interviews with four district officials coordinating and facilitating the district’s teacher induction programme. While it is apparent that beginner teacher induction is being prioritised due to the pressing need for South African teacher professional development initiatives to work more towards developing and strengthening a repertoire of sound instructional practices. Findings indicate that current teacher induction practices offered by the selected district are somewhat misaligned with this imperative. The teaching form and foci of the districts’ induction programme reveals serious contestation as pressure to perform is exerted rather than supporting teachers early in their careers. The activities therein are evidently more focused on familiarising beginner teachers with legal frameworks that govern and regulate their duties as members of the public service. Although the district induction programme has an overarching aim of developing beginner teachers’ pedagogical practices, upon implementation, the emphasis is on accountability and pressure at the expense of developmental support and capacity building.